Effectiveness Of Music Therapy In Reducing Low Back Pain Among Pregnant Women Third Trimester - Murbiah; Salsabila; Husin; Santhna Letchmi Panduragan (Jurnal Inspirasi Kesehatan, 2023)
Background: Pregnancy is a period that starts from conception to the birth of the fetus. Third trimester of pregnancy, which is the last 3 months of pregnancy which starts from the 28th week to the 40th week. (Setiawati et al., 2019). Physiological changes that occur during pregnancy have pathways that are pathological for pregnant women. Complaints in pregnant women include back pain which is characterized by the enlargement of the uterus affecting the center of gravity, stretching out and bandaging the abdominal muscles, changing body postures, and putting pressure on the back. Therapy Listening to music can produce endorphins (a morphine-like substance supplied by the body which can reduce pain/pain) which can inhibit the transmission of pain impulses in the central nervous system, so that the sensation of pain can be reduced Objective : To determine the effectiveness of the music therapy to reducing low back pain on pregnant women Methodology This study used a quantitative approach with a quasi-experimental design using a one group pretest posttest design. The sampling technique was perposive sampling in third trimester pregnant women, totaling 40 respondents. Result and Discussion: The results showed that the median pretest value was 6.00 and the median posttest value was 2.00 with a p value of 0.00 <0.05, this indicated that there was a decrease in back pain before and after the classical music therapy. Conclusion: Mozart classical music therapy has an effect on reducing back pain in third trimester pregnant women.